(untitled) (Indian Journal of Child Health, 2020)
Background: Respiratory distress syndrome (RDS) is the major cause of morbidity and mortality in preterm newborns. Continuous positive airway pressure (CPAP) acts by preventing atelectasis and improves functional residual capacity and arterial oxygenation. Aims: This study aims to evaluate the effectiveness of early nasal bubble CPAP in treating preterm neonates with mild-to-moderate RDS in the rural setting. Materials and Methods: It is a prospective analytic observational study done at a tertiary hospital in the rural area of southern India from December 2018 to December 2019. All babies between 28 and 34 weeks of gestation with mild and moderate RDS were included in the study. Babies with severe RDS requiring surfactant were excluded from the study. Results: Incidence of RDS among babies born between 28 and 34 weeks of gestation was 3.2%. Out of total 50 babies who were managed with early nasal CPAP, it proved effective in 43 babies (86%), while remaining 7 babies (14%) had to be intubated and required ventilation. Babies were studied based on radiological appearance and we found a success rate of 93.1% in moderate grade hyaline membrane disease (HMD) (p<0.005). Conclusion: Bubble CPAP is effective in treating mild and moderate cases of RDS at peripheral center and help decrease the burden at tertiary care center.